Who Is Considered Well Integrated? A Vignette Study About the Perception of Integration of Migrants - Pap Ilona (Sciendo, 2021)
This contribution examines the relevance of the cultural, social and structural dimension of integration for the total perception of integration of migrants by the population of Switzerland. By means of a vignette study we show in our model that language ability as an aspect of cultural integration is the strongest determinant for a positive perception of integration. Second is the social integration as measured by the participation in associations, followed by the structural integration. Nationality and religion have only little relevance.